THE ANALYSIS OF EFFECTS OF VOLUNTARY DISCLOSURE TO THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND EARNINGS MANAGEMENT - Fauzi -; Anuar Sanusi (Prosiding International conference on Information Technology and Business (ICITB), 2015)
This study is aimed at examining the relationshipbetween corporate governance mechanisms andearnings management with voluntary disclosure(voluntary disclosure) as a moderating variable.Corporate governance is proxied and measured byManagerial Ownership (MGR) Institutional Ownership(INST), board size (BSIZE), and the independentCommissioner (KI). Voluntary Disclosure of EarningsManagement proxied in this study uses the value ofdiscretionary accruals, and Voluntary Disclosure isproxied by the disclosure index. The population of thisstudy is all listed manufacturing companies in IndonesiaStock Exchange from 2006 to 2011.The results of this study are first, there is an empiricalevidence to suggest that there are negative effects ofdiscretionary accruals managerial ownership,institutional ownership and a positive influence on thesize of the board of directors. Overall, these results areconsistent with research conducted by Pranata (2003)and Rajgopal (1998) that managerial ownership andinstitutional ownership become a constraint on earningsmanagement practice. Second, testing the relationshipbetween voluntary disclosure mechanism betweencorporate governance and discretionary accruals indicatethat the earnings management practices will be carriedout if the company is getting a lot of information. Theseresults are consistent with the research conducted byAryati (2003). Third, the composition of theindependent commissioner was not statisticallysignificant to the earnings management measures, andvoluntary testing of these revelations on the relationshipbetween the practice of earnings management andcorporate governance mechanisms remains to show thatthe composition of an independent commissioner is notsignificant. This gives evidence that the ineffectivenessof the company's independent commissioner.KEYWORDS: Earnings management, VoluntaryDisclosure, Corporate Governance